1991
DOI: 10.1073/pnas.88.6.2297
|View full text |Cite
|
Sign up to set email alerts
|

Approximate entropy as a measure of system complexity.

Abstract: Techniques to determine changing system complexity from data are evaluated. Convergence of a frequently used correlation dimension algorithm to a finite value does not necessarily imply an underlying deterministic model or chaos. Analysis of a recently developed family of formulas and statistics, approximate entropy (ApEn), suggests that ApEn can classify complex systems, given at least 1000 data values in diverse settings that include both deterministic chaotic and stochastic processes. The capability to disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
3,325
5
86

Year Published

1992
1992
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 4,895 publications
(3,614 citation statements)
references
References 13 publications
27
3,325
5
86
Order By: Relevance
“…Normalizing r in this manner gives ApEn a translation and scale invariance, in that it remains unchanged under uniform process magnification, reduction, or constant shift to higher or lower values (Pincus, 2001). Moreover, several studies (Pincus, 1991;Pincus and Keefe, 1992) have demonstrated that these input parameters produce good statistical reproducibility for ApEn for time series of length N≥60, as considered herein. For this pilot study, ApEn was estimated with m=1 and r=0.2 times the SD of the original data sequence.…”
Section: Approximate Entropy (Apen)mentioning
confidence: 75%
See 3 more Smart Citations
“…Normalizing r in this manner gives ApEn a translation and scale invariance, in that it remains unchanged under uniform process magnification, reduction, or constant shift to higher or lower values (Pincus, 2001). Moreover, several studies (Pincus, 1991;Pincus and Keefe, 1992) have demonstrated that these input parameters produce good statistical reproducibility for ApEn for time series of length N≥60, as considered herein. For this pilot study, ApEn was estimated with m=1 and r=0.2 times the SD of the original data sequence.…”
Section: Approximate Entropy (Apen)mentioning
confidence: 75%
“…ApEn was introduced as a quantification of regularity in sequences and time series data, initially motivated by applications to relatively short, noisy data sets (Pincus, 1991). It is scale invariant and model independent, evaluates both dominant and subordinated patterns in data, and discriminates series for which clear feature recognition is difficult.…”
Section: Approximate Entropy (Apen)mentioning
confidence: 99%
See 2 more Smart Citations
“…The regularity of serum insulin concentration time series was assessed by application of Approximate Entropy (ApEn), which is a model independent statistic [27]. ApEn has been introduced to discriminate between insulin secretory profiles in glucose tolerant first degree relatives of Type 2 diabetic patients compared with healthy people [8].…”
Section: Spectral Analysismentioning
confidence: 99%